2019
DOI: 10.1093/tas/txz087
|View full text |Cite
|
Sign up to set email alerts
|

Branched-chain amino acid interactions in growing pig diets1

Abstract: The branched-chain amino acids (BCAA) Leu, Ile, and Val share the first steps of their catabolism due to similarities in their structure. The BCAA are reversibly transaminated in skeletal muscle through the activity of branched-chain aminotransferase and then transported to the liver. They undergo an irreversible decarboxylation catalyzed by the branched-chain α-keto acid dehydrogenase complex. Both enzymes are common to Leu, Ile, and Val and increased enzymatic activity stimulated by an excess of one of them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Among several potential mechanisms, including a leucine "desynchronization effect" (63) one possibility is that beyond a certain level, excess of leucine may stimulate key enzymes in BCAA catabolism (i.e., BCAA aminotransferase and branchedchain alpha-keto acid dehydrogenase) thus increasing the oxidation of serum leucine (79,80). Moreover, a surplus in leucine intake can decrease the plasma concentration of the other EAAs, an effect called BCAA antagonism (81)(82)(83). Further investigations are needed to confirm the "desynchronization effect" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among several potential mechanisms, including a leucine "desynchronization effect" (63) one possibility is that beyond a certain level, excess of leucine may stimulate key enzymes in BCAA catabolism (i.e., BCAA aminotransferase and branchedchain alpha-keto acid dehydrogenase) thus increasing the oxidation of serum leucine (79,80). Moreover, a surplus in leucine intake can decrease the plasma concentration of the other EAAs, an effect called BCAA antagonism (81)(82)(83). Further investigations are needed to confirm the "desynchronization effect" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, for N, there is strong interaction between AA such as valine, leucine, and isoleucine, the branched-chain amino acids required for protein synthesis but sharing the same enzymes for degradation with leucine that is generally in excess in swine diet ( NRC, 2012 ). Recently, studies showed that leucine excess may increase the need for dietary valine and Ile in piglets ( Cemin et al, 2019 ). For P, the interaction with calcium is well known and should be considered to optimize it’s use ( Létourneau-Montminy et al, 2012 ; NRC, 2012 ).…”
Section: Precise Estimation Of Animal Phosphorus and Nitrogen Require...mentioning
confidence: 99%
“…Recent developments in feed grade manufacturing of L-Val, and to a lesser extent L-Ile, have resulted in prices that allow for more feasible use in feed formulation. Subsequently, interest has grown to better understand how all BCAA interact with one another under commercial conditions, not only in poultry ( Ospina-Rojas et al, 2017 ; Ospina-Rojas et al, 2018 ; Zeitz et al, 2019 ; Ospina-Rojas et al, 2020 ) but other monogastric species as well ( Cemin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%